Cross-cultural adaptation and content validity of leisure attitude measurement for older adults - Vivian Carla de Castro; Fernanda Shizue Nishida; Flavia Maria Derhun; Anai Adario Hungaro; Eraldo Schunk Silva; Lígia Carreira (Universidade de São Paulo, 2020)
ABSTRACT OBJECTIVE: To adapt the Leisure Attitude Measurement to the Brazilian culture and to evaluate the face and content validity of the Brazilian version for older population. METHODS: Methodological study of cross-cultural adaptation in five stages: initial translation; synthesis of translations; back translation; evaluation by a committee of experts using a face and content validity assessment instrument; pre-test with 36 elderly, selected by convenience, with the application of a pre-test evaluation instrument. Data were analyzed descriptively and internal consistency measured by Cronbach's alpha coefficient. RESULTS: Evidenced face and content validity of the adapted version, as well as its equivalence with the original version. In the pretest, the elderly were 71.5 years old on average, 66.7% were women, 47.2% had a stable union, 66.7% lived with family members, 47.2% had 12 or more years of education and 58.3% received two minimum wages or more. The instrument revealed good internal consistency with a coefficient of 0.95 for the total global instrument and 0.88, 0.92 and 0.88 for the cognitive, affective and behavioral domains, respectively. CONCLUSIONS: The instrument's adaptation to the Brazilian culture was successful and allows to assess the attitude of the elderly in relation to leisure in a reliable manner, even though the results are a preliminary version, to be concluded after the psychometric analysis. The instrument could be incorporated in various health fields in Brazil and will allow the production of standardized data, comparison between cultures and strategies to promote positive attitudes towards leisure.